Estimating Annual Forage Yields with Plant Available Water and Growing Season Precipitation - J. Holman; A. Obour; A. Schlegel; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2019)
Forage production is important for the western Kansas region’s livestock and dairy industries and has become increasingly important as irrigation-well capacity declines. Forages require less water than grain crops and may allow for increased cropping intensity and opportunistic cropping. Being able to estimate forage production is important for determining forage availability versus forage needs. Data from several studies were used to quantify annual forage yield response to plant available water (PAW) at planting and growing season precipitation (GSP). In addition, water use efficiency was quantified. Forages evaluated included winter triticale, spring triticale, and forage sorghum. Preliminary results showed PAW and GSP explained 26% of the variability in forage sorghum yield. Winter triticale yield increased by 640 lb/a for every inch of water use (PAW plus GSP). However, spring triticale produced only 193 lb/a for every inch of water use. The low correlation with water use and spring triticale yield suggests other factors, such as temperature, affect spring forage production more than soil moisture.
Keywords: No-Till; Conventional Tillage; Soil Water; Grain Yield; available water; growing season precipitation